Read it yourself : Cars Level - 1 - ladybird (Bharat Ladybird, 2016)
Learn about lots of different cars$1 (Bbig cars, little cars, fast cars, and special cars. See what they look like and who drives them. For more than 35 years, the best-selling Read it yourself with Ladybird has helped children learn to read. All books feature essential key words. Title-specific words are repeated to practice throughout. Designed to be read independently at home or used in a guided reading session at school. All titles include comprehension puzzles, guidance notes, and book band information for schools. This Level 1 title is suitable for very early readers who are ready to take their first steps in reading real stories. Each simple story uses a small number of frequently repeated words.s
Keywords: Easy Read Nonfiction -- Easy Read Nonfiction